Chemical Shift magnetization transfer magnetic resonance imaging. Issue 2 (31st August 2016) - Li, Weiguo; Wang, Xifu; Miller, Frank H.; Larson, Andrew C.
Abstract : Purpose: The purpose of this work was to develop a chemical shift magnetization transfer (CSMT) magnetic resonance imaging (MRI) method to provide accurate magnetization transfer ratio (MTR) measurements in the presence of fat. Methods: Numerical simulations were performed to compare MTR measurements at different echo times (TEs) for voxels with varying fat/water content. The CSMT approach was developed using water fraction estimates to correct for the impact of fat signal upon observed MTR measurements. The CSMT method was validated with oil/agarose phantom and animal studies. Results: Simulations demonstrated that the observed MTRs vary with water fraction as well as with the TE‐dependent phase difference between fat and water signals; simulations also showed that a linear relationship exists between MTR and water fraction when fat and water signals are in phase. For phantom studies, observed MTR decreased with increasing oil fraction: 42.41 ± 0.54, 38.12 ± 0.33, 32.93 ± 0.56, and 26.08 ± 0.87 for 5% to 40% oil fractions, respectively, compared to 42.63 ± 1.04 for phantom containing 4% agarose only. These offsets were readily corrected with the additional acquisition of a water fraction map. Conclusion: Fat fraction and TE can significantly impact observed MTR measurements. The new CSMT approach offers the potential to eliminate the effects of fat upon MTR measurements. Magn Reson Med 78:656–663, 2017. © 2016 International Society for Magnetic Resonance in Medicine